The right to effective compensation from the municipality for failure to provide social housing (Ius Novum, 2024)
Article 1 of Protocol No. 1 to the Convention for the Protection of Human Rights and Fundamental Freedoms provides that every natural and legal person has the right to the peaceful enjoyment of his possessions. No one shall be deprived of his possessions except in the public interest and subject to the conditions provided for by law and in accordance with the general principles ofinternational law. The purpose of these laws is primarily to protect property. By recognizing that everyone has the right to respect for their possessions, Art. 1 of Protocol No. 1 to the Convention for the Protection of Human Rights and Fundamental Freedoms in fact guarantees the right to property, and deprivation of property is permissible only under certain conditions. In national jurisprudence, these guarantees are not sufficiently implemented. Although compensation is provided for by the commune (Article 18(3a) of the Act on the protection of tenants’ rights, housing resources of the municipality and amending the Civil Code). However, the courts are too strict in assessing the evidentiary requirements imposed on applicants. In the case of Wyszyński v. Poland, where the applicant had not been awarded domestic damages by the municipality for failing to provide social housing, the Court rightly noted that the courts assumed that the applicant had failed to prove that the damage suffered by him was the normal consequence of the municipality’s unlawful omission, although In the course of the proceedings, as many as two expert opinions were obtained. In the case of Broniowski v. Poland, in the area of property beyond the Bug River, it was clearly indicated that the taking of property without compensation in reasonable proportion to its value is usually considered a disproportionate interference, and a total absence of compensation can only be justified exceptionally. It also seems indispensable when assessing the existence of an adequate causal link to appeal in this respect, leaving it to the knowledge and life experience of the adjudicating panel, applied appropriately to the circumstances of the case. The requirements as to the proof of damage cannot be understood too strictly. There is a need to liberalize the evidentiary proceedings and make broader use of factual presumptions (Article 231 of the Code of Civil Procedure) as well as limiting the evidence to substantiation in order to ensure that the owner effectively seeks compensation from the commune for failure to provide social housing. Clear intervention by the legislator is necessary to overcome the defective court practice. It would be advisable to make an explicit procedural reference to the application of Art. in this category of cases. 322 of the Code of Civil Procedure not only in terms of the amount of damage but also the fact that it occurred.
Keywords: property law, respect for property, compensation, social housing, protection of tenants’ rights, owner, municipality, effective protection, damage, remedy